Spectral investigation of Yb3+/Ho3+/Tm3+:Y2Si2O7 upconverting nanophosphors for the usage of temperature sensing - ERDEM, MURAT; ESMER, KADİR (My University, 2023)
© 2023, Turkish Chemical Society. All rights reserved.Rare earth (Yb3+, Ho3+, Tm3+) yttrium disilicate phosphors were produced by sol-gel technique and heated at 1050 °C temperature. The sizes of the phosphors vary between 20-30 nm according to the images obtained from the Transmission Electron Microscope. The up-conversion (UC) emissions of the nanopowders were measured in the range of 500–900 nm wavelength under 950 nm laser excitation. A linear increase with power was observed in the emission intensity ratio depending on the laser excitation power. Using the FIR technique, the phosphor’s temperature was determined by the heating effect caused by the laser pump power. Due to the change in intensity ratio versus temperature, the temperature sensitivity at 428 K was calculated as 0.781x10-2K-1 and it was suggested that it can be used as a promising temperature sensor probe in photonic devices.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Natural Sciences (SCI); CHEMISTRY; Genel Kimya; Fizik Bilimleri; General Chemistry; Physical Sciences; Nanophosphors; Sol-gel; Temperature sensing; Up-conversion; Nanophosphors; Sol-gel; Up-conversion; Temperature sensing